2010
DOI: 10.1590/s0034-737x2010000600008
|View full text |Cite
|
Sign up to set email alerts
|

Preferência de Aphis craccivora por genótipos de feijão-caupi de porte prostrado, em Aquidauana, MS

Abstract: Preference of Aphis craccivora for prostrate cowpea genotypes, in Aquidauana, MSCowpea (Vigna unguiculata (L.) Walp.) is an important food source. However, there is a lack of studies on this crop in Midwestern Brazil. Experiments were conducted in field conditions in Aquidauana, Mato Grosso do Sul, aiming to find genotypes less preferred by black aphid (Aphis craccivora (Koch.)). In April and October 2009, 20 prostrate genotypes were sown, and after germination the number of females and colonies were counted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…It has been reported that trichomes did not affect the selection of host or the biology of the cotton aphid, Aphis gossypii Glöver on cotton [ 67 ], and the cowpea aphid, Aphis craccivora C.L. Koch on cowpea [ 68 ], and on lima bean [ 69 ]. However, leaf trichomes can mechanically disrupt the movement of insect herbivores on the leaf surface, thus reducing access to the food.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that trichomes did not affect the selection of host or the biology of the cotton aphid, Aphis gossypii Glöver on cotton [ 67 ], and the cowpea aphid, Aphis craccivora C.L. Koch on cowpea [ 68 ], and on lima bean [ 69 ]. However, leaf trichomes can mechanically disrupt the movement of insect herbivores on the leaf surface, thus reducing access to the food.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, a Tabela 2 -Número médio de adultos (NA) e ninfas (NN) e relação número de ninfas / número de adultos (NN/NA) de Aphis craccivora em genótipos de Vigna unguiculata, 48 horas após infestação, em teste com chance de escolha Corroborando com os resultados encontrados nesse trabalho, Rodrigues et al (2010) verificaram baixas infestações de A. craccivora em BRS Guariba. Em condições de campo, Bandeira et al (2015) observaram que genótipos BRS Cauamé e BRS Guariba apresentaram os menores índices de infestação por A. craccivora, sugerindo a existência de resistência do tipo não preferência.…”
Section: Resultsunclassified